MicroRNA‐dependent regulation of KLF4 by glucose in vascular smooth muscle. Issue 9 (25th March 2018) - Hien, Tran T.; Garcia‐Vaz, Eliana; Stenkula, Karin G.; Sjögren, Johan; Nilsson, Johan; Gomez, Maria F.; Albinsson, Sebastian
Abstract : Diabetes is a major risk factor for cardiovascular disease and this is in part due to the effects of hyperglycemia on vascular smooth muscle cells. Small non‐coding microRNAs are known to control smooth muscle phenotype and arterial contractility and are dysregulated in diabetes. The effect of microRNAs on smooth muscle differentiation is in part mediated by the transcription factor KLF4 but the role of this mechanism in diabetic vascular disease is not fully understood. Herein, we have investigated the importance of hyperglycemia and diabetes for the expression of KLF4 in vascular smooth muscle and the involvement of miRNAs in this regulation. Hyperglycemia down‐regulated KLF4 in vascular smooth muscle cells and similar results were found in arteries of diabetic mice and patients. This correlated with a Foxa2‐dependent up‐regulation of miR‐29c, which targeted KLF4 in vascular smooth muscle cells. Importantly, by preventing downregulation of KLF4, the induction of smooth muscle contractile protein markers by glucose was inhibited. In conclusion, miR‐29 mediated inhibition of KLF4 in hyperglycemic conditions contributes to increased expression of contractile markers in vascular smooth muscle cells. Further studies are warranted to determine the therapeutic implications of miR‐29 inhibition in diabetic vascular disease. Abstract : Elevated glucose levels can increase expression of contractile proteins in vascular smooth muscle cells. This effect is associated with increased miR‐29 expression and downregulation of its target KLF4. The reduced expression of KLF4 is necessary, but not sufficient, for the effects of glucose in smooth muscle.